Riesz means on homogeneous trees - Papageorgiou Effie (De Gruyter, 2021)
Let 𝕋 be a homogeneous tree. We prove that if f ∈ Lp(𝕋), 1 ≤ p ≤ 2, then the Riesz means SzR (f) converge to f everywhere as R → ∞, whenever Re z > 0.